Degree of Postoperative Curve Correction Decreases Risks of Postoperative Pneumonia in Patients Undergoing Both Fusion and Growth-friendly Surgical Treatment of Neuromuscular Scoliosis. Issue 7 (17th August 2022) - Levine, Sonya B.; Fields, Michael W.; Boby, Afrain Z.; Matsumoto, Hiroko; Skaggs, Kira F.; Roye, Benjamin D.; Vitale, Michael G.
Abstract : Introduction: Due to a combination of poor respiratory muscle control and mechanical lung compression secondary to spine and chest wall deformities, patients with neuromuscular (NM) early-onset scoliosis (EOS) are at a high risk for pulmonary complications including pneumonia. The purpose of this study is to examine the effect of surgical intervention on the prevalence and risk of postoperative pneumonia in patients with NM EOS. Methods: In this retrospective cohort study, pediatric (18 y old and below) patients with NM EOS undergoing index fusion or growth-friendly instrumentation from 2000 to 2018 were identified. Patients were then categorized into 2 groups: those with ≥50% curve correction and those with <50% curve correction of the coronal deformity at the first postoperative visit. The primary outcome of interest was postoperative pneumonia occurring between 3 weeks and 2 years postoperatively. Manual chart review was supplemented with phone call surveys to ensure all occurrences of preoperative/postoperative pneumonia (ie, in-institution and out-of-institution visits) were accounted for. Results: A total of 35 patients (31% female, age at surgery: 10.3±4.3 y) with NM EOS met inclusion criteria. Twenty-three (66%) patients experienced at least 1 case of preoperative pneumonia. Twenty-six (74%) patients had ≥50% and 9 (26%) patients had <50% immediate postoperative curve correction. In total, 12 (34%) patients experienced at least 1 case of postoperative pneumonia (7 in-institution, 5 out-of-institution). Seven (27%) patients with ≥50% curve correction versus 5 (56%) with <50% curve correction experienced postoperative pneumonia. Relative risk regression demonstrated that patients with <50% curve correction had increased risk of postoperative pneumonia by 2.1 times compared with patients with ≥50% curve correction (95% confidence interval: 0.9; 4.9, P =0.099). Conclusion: The prevalence of preoperative and postoperative pneumonia is high in patients with NM EOS. This study presents preliminary evidence suggesting that percent curve correction is associated with the occurrence of postoperative pneumonia in patients with NM EOS undergoing surgical correction.